2020
DOI: 10.1002/jcp.29877
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 deficiency exacerbates cardiac fibrosis after myocardial infarction by promoting endothelial‐to‐mesenchymal transition

Abstract: Cardiac fibrosis is a reparative process after myocardial infarction (MI), which leads to cardiac remodeling and finally heart failure. Endothelial-to-mesenchymal transition (EndMT) is induced after MI and contributes to cardiac fibrosis after MI. Orphan nuclear receptor Nur77 is a key regulator of inflammation, angiogenesis, proliferation, and apoptosis in vascular endothelial cells. Here, we investigated the role of orphan nuclear receptor Nur77 in EndMT and cardiac fibrosis after MI. Cardiac fibrosis was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…While the role of Nur77 in epicardial cells was not studied here, it may also be of interest in relation to the fibrotic response and rupture after MI in Nur77-KO mice, since we have observed high Nur77 expression in epicardial cells upon MI in mice (data not shown). We furthermore cannot exclude the influence of proinflammatory macrophages and endothelial cells on myocardial thinning and rupture in our MI experiments with ApoE/Nur77-KO mice [24,34,36]. However, in the one-week model of ISO-induced cardiac hypertrophy, where monocyte infiltration, macrophage accumulation, and the expression of proinflammatory genes are not prominent, Nur77-KO mice also exhibit severe myocardial thinning, rupture and reduced scar density.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…While the role of Nur77 in epicardial cells was not studied here, it may also be of interest in relation to the fibrotic response and rupture after MI in Nur77-KO mice, since we have observed high Nur77 expression in epicardial cells upon MI in mice (data not shown). We furthermore cannot exclude the influence of proinflammatory macrophages and endothelial cells on myocardial thinning and rupture in our MI experiments with ApoE/Nur77-KO mice [24,34,36]. However, in the one-week model of ISO-induced cardiac hypertrophy, where monocyte infiltration, macrophage accumulation, and the expression of proinflammatory genes are not prominent, Nur77-KO mice also exhibit severe myocardial thinning, rupture and reduced scar density.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown that Nur77 deficiency in monocytes and macrophages promotes a proinflammatory phenotype, leading to impaired myocardial repair and larger scar size with reduced collagen density after MI [24,33]. Furthermore, Nur77 was shown to repress endothelial-to mesenchymal transition, leading to enhanced MI-induced fibrotic scar size in Nur77-KO mice [34]. Additionally, epicardial cells are thought to be involved in myocardial repair responses after MI by giving rise to cardiac myofibroblasts through epithelial-mesenchymal transition [7,35].…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2003, Kuwahara et al (41) observed that the TGF-β signaling pathway is important in cardiac fibrosis and diastolic heart failure in rats and that altering the activity of this pathway inhibits the progression of cardiac fibrosis. Recent studies have shown that the EndMT is associated with heart failure (20,(42)(43)(44) and is also crucial in cardiac fibrosis following myocardial infarction (45). Cardiac function can be improved by inhibiting EndMT (46).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the process of myocardial fibrosis can be controlled by the regulation of EMT. Chen et al [ 78 ] found that NUR77, an orphan nuclear receptor, inhibits EMT and thus regulates myocardial fibrosis. Yin et al [ 79 ] found that Tongxinluo, a common drug used to treat cardiovascular disease, enhanced the expression of endothelial markers in VECs and inhibited EMT.…”
Section: Clinical Prospectsmentioning
confidence: 99%